أدوات استعباد المجتمعات من خلال تفسير (في ظلال القرآن) لسيد قطب - عودة, عبد الله (University of Eloued جامعة الوادي, 2021)
ملخص يعالج هذه الدراسة موضوع أدوات استعباد المجتمعات من خلال تفسير (في ظلال القرآن) لسيد قطب، وعلاقتها بالواقع وخطورتها على الأمة، متبعا المنهج الوصفي والمنهج التحليلي. وجاءت الدراسة في تسع مباحث، أولها التعريف بالاستعباد، ثم كانت بقية المباحث في بيان أدوات الاستعباد الثمانية التي بينها سيد قطب في تفسيره. وقد توصلت الدراسة إلى أن تفسير سيد قطب أولى قضايا المجتمع أهمية كبيرة، وبذل وسعه لربط تفسير القرآن بقضايا الأمة، وأن قضية تحرير الشعوب من الاستعباد كانت من المحاور البارزة في تفسيره، وأن من أخطر أدوات استعباد الشعوب: تغييب الوعي، وتوظيف علماء السلاطين، وإشاعة الفاحشة، واستخدام المال والإعلام، ونشر الخرافات والشركيات، وغيرها. Tools of dominating societies through Tafsir “Fi Zilal Al-qur'an” by Sayyid Qutb Abstract The purpose of this study is to discuss the issue of dominating (enslaving) societies through Fi Zilal Al-Qur'an interpretation by Sayyid Qutb, and its relationship to reality and danger to the nation, following the descriptive and analytical method. This research came in nine sections, the first of which was the definition of enslavement, then the rest of the sections dealt with the eight tools of enslavement that Sayyid Qutb explained in his Tafsir. The study concluded that Sayyid Qutb’s interpretation of the issues of society is of great importance, and he exerted his effort to link the interpretation of the Qur’an with the issues of the nation and that the issue of liberating people from enslavement was one of the prominent axes in its interpretation. The most important tools of enslavement of people are lack of awareness, corrupt scholars, the spread of obscenity, the use of money and the media, the dissemination of myths and polytheism, and others
مقال